2007
DOI: 10.1002/ijc.22550
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of hyaluronan synthase 2 suppresses the malignant phenotype of invasive breast cancer cells

Abstract: Accumulation of hyaluronan has been demonstrated in the peritumoral breast cancer stroma and nests of tumor cells. In this study, we have quantified the production of hyaluronan and the expression of mRNAs encoding hyaluronan synthesizing (HAS) and hyaluronan degrading (HYAL) enzymes in a panel of breast cancer cell lines. The analysis revealed that highly invasive breast cancer cells produce high amounts of hyaluronan and express preferentially HAS2 mRNA, whereas less invasive breast cancer cells produce low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
134
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(156 citation statements)
references
References 46 publications
16
134
0
3
Order By: Relevance
“…In this study, we showed that 4-MU treatment in CF33 cells resulted in inhibition of cell growth associated with downregulation of HAS2 mRNA expression. Our data are consistent with a recent report showing that HAS2 is related to inhibition of cell proliferation, migration and metastasis in human breast cancer cells (35). Therefore, 4-MU may also serve as a potential therapeutic agent for breast cancer in dogs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, we showed that 4-MU treatment in CF33 cells resulted in inhibition of cell growth associated with downregulation of HAS2 mRNA expression. Our data are consistent with a recent report showing that HAS2 is related to inhibition of cell proliferation, migration and metastasis in human breast cancer cells (35). Therefore, 4-MU may also serve as a potential therapeutic agent for breast cancer in dogs.…”
Section: Discussionsupporting
confidence: 93%
“…A possible explanation for the results of our study is that 4-MU causes positive feedback for HAS3 mRNA expression to compensate for the inhibition of HA synthesis. These observations are likely to occur in HA-associated genes (17,35). Our results further showed that the downregulation of HAS2 after treatment with 4-MU induced marked growth retardation and apoptosis in CF33 cells.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…HAS1 and HAS2 produce HA of 200-2000 kDa, whereas HAS3 mainly synthesizes HA of 100-1000 kDa (14). Knockdown of the HAS genes in tumor cells was reported to inhibit their proliferation, invasion and motility in vitro and tumor growth and metastasis in vivo (16)(17)(18)(19)(20)(21)(22). In particular, it has been reported that the levels of HAS2 expression are often correlated with malignant behavior in various cancer cells such as breast cancer, fibrosarcoma and osteosarcoma cells (17,(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%